Study on the Acceptance of Contraceptive Devices Among Married Female Workers of a Garments Factory of Dhaka City - Begum, Mahjabeen Sultana; Hussain, Md Altaf (Bangladesh Journal of Physiology and Pharmacology, 2010)
Over the last decade, the number of garments factories in Bangladesh had increased and employed around 1.5 million women, most of them in their reproductive age, therefore, desired family size and child spacing influenced contraceptive prevalence among the married women. This cross sectional study was conducted in Chancellor Garments Factory, Rayer Bazar, Dhaka, to find out the acceptance of contraceptive methods among the married female workers. Out of 121 workers interviewed, the knowledge of respondents on contraceptive methods was found adequate in 83.47%, some knowledge in 15.70% and no knowledge in 0.83%. 27.5% respondents acquired their knowledge from clinics and 25.83% from health workers. Only 13.22% respondents had the knowledge on non contraceptive uses of condom and 50% of them got this knowledge from radio and television. Of the 88.43% respondents who used contraceptive devices, maximum number used oral pill (57.94%) and only 0.93% used condom. Among the non users of contraceptive methods, 28.56% did not use because their husbands did not agree. Among the contraceptive users, 90.65% had consent of both the partners and 2.8% had the desire of their husbands only. Low income, lack of motivation by health workers, lack of information on contraception, less accessibility and availability of devices, cost of the devices, side effects, misconception, etc. have the impact on the contraceptive acceptance among the female garments workers. Key words: Married female workers, Garments factory, Acceptance of contraceptive method. DOI: 10.3329/bjpp.v24i1.5731 Bangladesh J Physiol Pharmacol 2008; 24(1&2) : 10-13